Support for smoke-free policies in the Cyprus hospitality industry - Lazuras, Lambros; Savva, Christos S.; Talias, Michael A.; Soteriades, Elpidoforos Soterakis (My University, 2015)
Objectives The present study used attitudinal and behavioural indicators to measure support for smoke-free policies among employers and employees in the hospitality industry in Cyprus. Methods A representative sample of 600 participants (95% response rate) completed anonymous structured questionnaires on demographic variables, smoking status, exposure to second-hand smoke at work and related health beliefs, social norms, and smoke-free policy support. Results Participants were predominantly males (68.3%), with a mean age of 40 years (SD = 12.69), and 39.7%were employers/owners of the hospitality venue. Analysis of variance showed that employers and smokers were less supportive of smoke-free policies, as compared to employees and non-smokers. Linear regression models showed that attitudes towards smoke-free policy were predicted by smoking status, SHS exposure and related health beliefs, and social norm variables. Logistic regression analysis showed that willingness to confront a policy violator was predicted by SHS exposure, perceived prevalence of smoker clients, and smoke-free policy attitudes. Conclusions SHS exposure and related health beliefs, and normative factors should be targeted by interventions aiming to promote policy support in the hospitality industry in Cyprus.
Keywords: Cyprus; Hospitality industry; Policy support; Smoke-free policies